How Women Are Treated During Facility-Based Childbirth in Four Countries: A Cross-sectional Study With Labour Observations and Community-Based Surveys. Issue 4 (April 2020) - Bohren, Meghan A.; Mehrtash, Hedieh; Fawole, Bukola; Maung, Thae Maung; Balde, Mamadou Dioulde; Maya, Ernest; Thwin, Soe Soe; Aderoba, Adeniyi K.; Vogel, Joshua P.; Irinyenikan, Theresa Azonima; Adeyanju, A. Olusoji; Mon, Nwe Oo; et al.
Abstract : (Abstracted from Lancet 2019;394:1750–1763) Women around the world experience mistreatment during childbirth. This includes, but is not limited to, physical abuse, verbal abuse, discrimination, and procedures performed without consent.